Youth Gang Names in Palu City: An Anthropolinguistic Study - Syamsuddin; Romadon, Mochammad Muchhlis (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2023)
During the 1990s, Palu City witnessed a notable social phenomenon characterized by the emergence of various youth gangs. These gangs adopted diverse names, incorporating elements such as the Kaili language, foreign languages, and acronyms. The primary aim of this research is to scrutinize the nomenclature of youth gangs in Palu City through the analytical lens of anthropological linguistics. The data collection methodology employed in this study featured the researcher as the principal instrument, involving the recording and observation of youth gang names in Palu City. The analytical approach applied in this research encompassed a systematic and objective content analysis. The outcomes of the study unveiled linguistic phenomena, including (1) the utilization of the Kaili language, (2) the incorporation of foreign languages, (3) the adoption of acronyms, and (4) instances of language resistance evident in the naming practices of youth gangs in Palu City.